(untitled) - Takezawa, Shin-ichi (Tokyo, 1981)
This book introduce about industrial relations since 1945. Managemetn enemy or partner. Acceptance of managemetn authority. Community relations in the company. Commitment to the company.
Keywords: Quản trị công nghiệp,Industrial management